2010
DOI: 10.1007/s10658-010-9606-0
|View full text |Cite
|
Sign up to set email alerts
|

Benomyl sensitivity assays and species-specific PCR reactions highlight association of two Colletotrichum gloeosporioides types and C. acutatum with rumple disease on Primofiori lemons

Abstract: Rumple is a serious peel collapse of Primofiori lemons in the southeast of Spain with an unresolved aetiology. Symptoms typically occur on fruits at ripening under wet conditions as dark sunken lesions producing premature fruit drop and damaged fruits unacceptable for fresh commercialization. A total of 16 Colletotrichum spp. isolates established from rumple-affected lemons collected during the autumn of 2007 from two different orchards were characterized by molecular and phenotypic assays and compared with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…A first important step is to identify the true species present in orchards. Colletotrichum species differ in pathogenicity and in their response to fungicides, making it necessary to study fungicide sensitivity (Adaskaveg and Hartin 1997;Bernstein et al 1995;Bragança et al 2016;Freeman et al 1998;Peres et al 2002Peres et al , 2004Valero et al 2010;Velho et al 2014;Munir et al 2016). By doing this, management in orchards can be optimized.…”
Section: Introductionmentioning
confidence: 99%
“…A first important step is to identify the true species present in orchards. Colletotrichum species differ in pathogenicity and in their response to fungicides, making it necessary to study fungicide sensitivity (Adaskaveg and Hartin 1997;Bernstein et al 1995;Bragança et al 2016;Freeman et al 1998;Peres et al 2002Peres et al , 2004Valero et al 2010;Velho et al 2014;Munir et al 2016). By doing this, management in orchards can be optimized.…”
Section: Introductionmentioning
confidence: 99%
“…The results of our study show that, based on mycelial growth, the isolates from both strawberry producing areas showed ED 50 no higher than 3 µg mL -1 . For this reason, it may be considered that C. acutatum populations have moderate resistance to benzimidazole fungicides such as thiophanate methyl, and more likely to benomyl, because of they share the same mode action, as previously shown (Peres et al, 2004;Valero et al, 2010). These results suggest the need to implement , estos últimos aislados tuvieron mutaciones de punto en el gen TUB2.…”
Section: Distribución De La Sensibilidad De Aislados De C Acutatum Amentioning
confidence: 71%
“…En el mismo sentido, Kim et al (2007) reportaron DE 50 entre 3.8 y 8.8 µg mL -1 en aislados de C. acutatum de chile con concentraciones de más de 100 µg mL -1 , pero no encontraron mutaciones puntuales en el gen TUB2. Los resultados obtenidos en nuestro estudio indican que en los aislados de ambas zonas productoras de fresa con base en el crecimiento micelial, las DE 50 no superaron los 3 µg mL -1 , por lo que puede considerarse que las poblaciones de C. acutatum manifiestan una resistencia moderada a fungicidas benzimidazoles como el metil tiofanato, y muy probablemente al benomil, dado el mismo modo de acción como se ha demostrado previamente (Peres et al, 2004;Valero et al, 2010). Estos resultados sugieren la necesidad de implementar estrategias de manejo de resistencia a benzimidazoles en las zonas de estudio dada la estabilidad que se ha aso- benzimidazole resistance management strategies in the study areas given the stability found in some fungi such as Botrytis cinerea (Hollomon, 2015); among these strategies are the use of fungicide mixtures or alternating fungicides of different mode of action and not using them for eradication purposes (after symptom development) (Brent and Derek, 2007).…”
Section: Distribución De La Sensibilidad De Aislados De C Acutatum Aunclassified
“…The yearly fluctuation of the incidence of rumple has led some to postulate that climatic conditions could be responsible (Knorr & Koo 1969;Alarcón et al 1996;Del Rivero 1967). Recently, fungal populations were reported to be associated with the disorder (Valero et al, 2010). However, a fungal infection seems to be an association or a secondary infection of weakened tissue rather than the causative agent of the disease.…”
Section: Rumple Of Lemonmentioning
confidence: 99%